Effect of the addition of ZnO seeds on the electrical proprieties of ZnO-based varistors - Souza, F. L.; Gomes, J. W.; Bueno, Paulo Roberto [UNESP]; Cassia-Santos, M. R.; Araujo, A. L.; Leite, E. R.; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Elsevier B.V., 2003)
ZnO has the characteristic of presenting an intermediate value for the effective 3 eV barrier at room temperature. ZnO ceramics are applied in high-voltage systems or circuits. Attempts were made to reduce the number of effective barriers in the system by adding large particles of ZnO to the varistor composition. This procedure reduced the breakdown field of the varistors by values up to 90% lower than those initially obtained, and produced nonlinear coefficients as low as 20. (C) 2003 Elsevier B.V. B.V. All rights reserved.
Keywords: ohmic properties; varistor; zinc oxide; ZnO seeds